EARLY ONSET CHRONIC TOPHACEOUS GOUT: CASE REPORT - O. Hakan Gündüz,; Lale Yılmaz,; Hatice Bodur,; Nalan Akyürek, (Archives of Rheumatology, 2001)
The typical gout patient is easily recognized: There is a sudden onset of severe pain and redness in the toe of a middle-aged and obese man, who is fond of eating and alcohol. It has been known since the time of Hippocrates that gout is very rare in young men and premenopausal women. Development of gout in a male patient under 30 years of age may indicate an enzyme defect that results in overproduction of purines or a hereditary renal tubular disease. Early recognition of these cases is important for preventing complications like nephrolithiasis and renal failure. In this report we presented a young male patient with gout, who had his first attack at the age of 15, and discussed early onset chronic tophaceous gout in the light of the literature.